Frugivory and Seed Dispersal by Carnivorans - Draper, John P.; Young, Julie K.; Schupp, Eugene W.; Beckman, Noelle G.; Atwood, Trisha B. (Frontiers in Ecology and Evolution, 2022)
Seed dispersal is critical to the ecological performance of sexually reproducing plant species and the communities that they form. The Mammalian order Carnivora provide valuable and effective seed dispersal services but tend to be overlooked in much of the seed dispersal literature. Here we review the literature on the role of Carnivorans in seed dispersal, with a literature search in the Scopus reference database. Overall, we found that Carnivorans are prolific seed dispersers. Carnivorans’ diverse and plastic diets allow them to consume large volumes of over a hundred families of fruit and disperse large quantities of seeds across landscapes. Gut passage by these taxa generally has a neutral effect on seed viability. While the overall effect of Carnivorans on seed dispersal quality is complex, Carnivorans likely increase long-distance dispersal services that may aid the ability of some plant species to persist in the face of climate change.